“A streetcar named desire” and its translation into Polish by Jacek Poniedziałek - Kosman, Marcin (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
Indubitably, Tennessee Williams is one of the most influential playwrights of the 20th century. Despite his grand popularity only two plays had been translated before Jacek Poniedziałek published his collection. The aim of the paper is to show the translation strategies implemented by the translator and comment on the validity of his choices. In contrast to Kazimierz Piotrowski and Eugeniusz Cęcalski, Poniedziałek preserves vernacular language and often adds words or phrases that could not have been uttered in the forties. This provokes a question what kind of language is spoken in Poniedziałek’s Streetcar. In my research I try to find these elements of the play which might have been lost in the sphere of drama translation. Moreover, I will compare Poniedziałek’s strategy with a more conservative approach taken by the previous translator.